Assessment of Pain and Dependency Levels in Patient with Paralytic Ileus Associated with Prolonged Antacid Use: Case Report - Syifaurrahmah, Syifaurrahmah; Perbrianti, Sandra; Nursiswati, Nursiswati (Journal of Nursing Care, 2025)
Paralytic ileus is a disorder that results in a halt of intestinal flow, causing fluid and gas accumulation. Although paralytic ileus is commonly associated with postoperative conditions, it may also influenced by electrolyte imbalances from long-term antacid use and age-related factors that increase mortality risk. If inadequately unmanaged, the condition can result in significant pain, increased risk of complications, and greater care dependency. The purpose to describe a case of paralytic ileus in an elderly patient with long-term antacid use and evaluate changes in pain intensity and care dependency during treatments. This case report involved a 74-year-old male patient with paralytic ileus and a primary nursing diagnosis of acute pain. Pain intensity and care dependency were assessed using the Numeric Rating Scale and Care Dependency Scale during a four-day hospitalization period. The patient showed clinical improvement, include the return of flatus and defecation, normalization of electrolyte levels, reduced pain intensity (NRS 6 to 3), and increased independence (CDS 46 to 62). Discussion: Nursing care included electrolyte correction and pain management through pharmacological therapy and guided imagery, which contribute to decreased pain an improved care dependency, particularly in continence-related aspects. Recall bias related medication history was identified as a limitation. This case underscores the importance of early recognition of electrolyte imbalance and comprehensive nursing assessment in patients with paralytic ileus. Holistic nursing care supported by multidisciplinary collaboration and non-pharmacological intervention played a critical role in enhancing patient outcomes and promoting functional independence during hospitalization.